Soundjata ou l’épopée mandingue: de la transmisión oral a la publicación en francés - Montes, Vicente Enrique (Anales de Filología Francesa, 2018)
This article aims to present Soundjata ou l’épopée mandingue (1960), of D. T. Niane, an epic story that tells the deeds of Soundjata, a hero who glorified the big Mandinka empire in the 13th century, not only through the griot poets’ words, but also thanks to his own creative work. To this end, we compare this literary work with another version of this epic story, L’épopée de Sunjara d’après Lansine Diabaté de Kéla (Malí) (1995), collated, transcribed and translated by Jansen, Duintjer and Tamboura, much closer to the oral sources than the story of Niane. Soundjata ou l’épopée mandingue, like other versions of the epic poem, has been published in French and thanks to this language the Mandinka monarch’s adventures crossed the boundaries of the African continent.